The organisation of urban public transport systems in Western European metropolitan areas
The structure-conduct-performance paradigm is applied to organisation change in urban public transport in Western Europe, to show how structural form affects public transport conduct and performance. This paper outlines organisation changes in several western European metropolitan areas, with reference to four common structural forms, and indicates expected changes in market conduct and performance.